Enlightening the structural, elastic, and luminescence properties of transparent Zn2SiO4 glass-ceramic by precipitation of Gd2O3 as dopant - Ismail, Nur Atikah Nazihah; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Yap, Wing Fen; Zalamin, Siti Norul Fadhilah; Mohamad Yamin, Nurul Afiqah (Elsevier BV, 2022)
This work focus on fabrication of new Gd3+-doped willemite (Zn2SiO4) glass-ceramics derived from the Gd2O3–ZnO–Al2O3–B2O3–SiO2 (Gd-ZABS) glass system by a controlled sintering process. The physical characteristic with formation of Gd3+-doped Zn2SiO4 glass-ceramic crystal phase, morphology and structural changes were examined by Archimedes method, X-ray diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and Fourier-transform infrared (FTIR) reflection spectroscopy. The appearance of SiO2, ZnO4 and Zn–O–Si bands indicate that the formation of Zn2SiO4 crystal phase. As for elastic analysis, the ultrasonic velocity and elastic coefficients showed an increasing tendency with the increase in sintering temperature. The study on energy transfer has found that the optical band gap of Gd3+-doped Zn2SiO4 glass-ceramic has decreased as the sintering temperature increased. The luminescence spectra of Gd3+-doped Zn2SiO4 exhibit several strong emission peak located at 425, 447, 462, 485 and 530 nm after the samples were subjected to 310 nm excitation source. Prominent green emission of Gd3+-doped Zn2SiO4 glass-ceramic were strongly observed at 530 nm. These spectra show that when the sintering temperature increases, the luminescence performance of the glass-ceramics has improved.